Severe Anemia in an Adolescent Male With Sickle Cell Trait. Issue 1 (January 2015) - Chapa-Rodriguez, Adrian; Dighe, Dipti; Giordano, Lisa
<x xml:space="preserve">Abstract</x> Background: Sickle cell trait is generally considered a benign condition. However, it has been associated with uncommon comorbidities such as painless gross hematuria secondary to renal papillary necrosis and renal medullary carcinoma. Observation: We present a 16-year-old African American boy with sickle cell trait and a recent history of prolonged gross hematuria due to renal papillary necrosis. The patient developed severe iron deficiency anemia and required transfusion support. Conclusions: Although renal papillary necrosis is well-described, it is uncommon in pediatrics and only rarely results in the need for transfusion.